DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE TEACHERS IN COMPUTER GRAPHICS (ResearchJet Journal of Analysis and Inventions, 2023)
The formation of professional qualities and professional competency qualities of future teachers. The identification of a system of pedagogical conditions and means that occupy a specific place in the formation of professional qualities of the future teacher in pedagogical institutions ensures the effective and correct Organization of the educational process.